2019
DOI: 10.1111/jcmm.14642
|View full text |Cite
|
Sign up to set email alerts
|

S100‐A9 protein in exosomes derived from follicular fluid promotes inflammation via activation of NF‐κB pathway in polycystic ovary syndrome

Abstract: Exosomes have recently emerged as key mediators of different physiological and pathological processes. However, there has been few report about proteomic analysis of exosomes derived from human follicular fluid and their association with the occurrence of PCOS. Herein, we used TMT‐tagged quantitative proteomic approach to identify proteomic profiles in exosomes derived from follicular fluid of PCOS patients and healthy controls. We identified 662 proteins in exosomes derived from human ovarian follicular fluid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 59 publications
3
66
0
Order By: Relevance
“…p < 0.05 (*) was considered significant. The PPI network of DEGs with combined score > 0.7 was built by STRING v11.0 and visualized by Cytoscape v3.7.2 [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…p < 0.05 (*) was considered significant. The PPI network of DEGs with combined score > 0.7 was built by STRING v11.0 and visualized by Cytoscape v3.7.2 [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…They demonstrated that EVs released from polymorphonuclear leukocytes by healthy volunteers could induce endothelial cells to produce cytokines and chemokines in vitro . In follicular fluids of PCOS women, Li et al (2019) used a tandem mass tag quantitative proteomic approach and found that follicular fluid exosomes of both normal and PCOS samples contained S100 calcium-binding protein A9 (S100-A9). S100-A9 expression was greater in the follicular fluid exosomes of PCOS women and enhanced inflammation and disrupted steroidogenesis by activating the nuclear factor kappa B (NF-κB) signaling pathway.…”
Section: Extracellular Vesicles and Polycystic Ovary Syndromementioning
confidence: 99%
“…In basic research, on the one hand, EVs contribute to disease pathophysiology. EVs and cargos include protein, miRNAs and lncRNAs that promote the development of the disease by influencing inflammation, angiogenesis, steroidogenesis and macrophage phagocytic ability ( Mesri and Altieri, 1998 ; Boilard et al, 2010 ; Harp et al, 2016 ; Munros et al, 2017 ; Gomes de Andrade et al, 2018 ; Khalaj et al, 2019 ; Li et al, 2019 ; Qiu et al, 2019 ; Sun et al, 2019 ). This effect may be mediated by the NF-κB signaling pathway ( Li et al, 2019 ; Zhang et al, 2019 ).…”
Section: Extracellular Vesicles Application In Clinical and Basic Resmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no comprehensive analysis of the bovine ffEV protein cargo has yet been performed. In contrast, the protein cargo of ffEVs has been assessed in equine and human ffEVs, and 73 and 662 proteins were identified, respectively ( 20 , 29 ). Moreover, a comparison of the abundance of ffEV proteins in control and polycystic ovary syndrome ovaries could potentially identify potential markers of oocyte quality ( 29 ).…”
Section: Introductionmentioning
confidence: 99%